The "strategy of freedom" in the Middle East: The rhetoric and reality of US policy - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2004)
In two policy speeches made in November 2003, President Bush reaffirmed and ex-plained his commitment to promoting democracy in the Middle East as a central goal of US foreign policy. Like no president before him, he has called for overcoming the failed, decades-old policy that has been primarily directed towards ensuring the stability of friendly autocratic states. The Bush administration considers a 'forward strategy of freedom' in the Middle East a central element of the war on terrorism. What does this policy really look like? What assumptions is it based on? What are the problems associated with it? (SWP Comments / SWP)
Keywords: 320